The European multicenter trial on the safety and efficacy of guided oblique lumbar interbody fusion (GO-LIF) - Birkenmaier Christof; Suess Olaf; Pfeiffer Michael; Burger Ralf; Schmieder Kirsten; Wegener Bernd (BMC Musculoskeletal Disorders, 2010)
Abstract Background Because of the implant-related problems with pedicle screw-based spinal instrumentations, other types of fixation have been tried in spinal arthrodesis. One such technique is the direct trans-pedicular, trans-discal screw fixation, pioneered by Grob for spondylolisthesis. The newly developed GO-LIF procedure expands the scope of the Grob technique in several important ways and adds security by means of robotic-assisted navigation. This is the first clinical trial on the GO-LIF procedure and it will assess safety and efficacy. Methods/Design Multicentric prospective study with n = 40 patients to undergo single level instrumented spinal arthrodesis of the lumbar or the lumbosacral spine, based on a diagnosis of: painful disc degeneration, painful erosive osteochondrosis, segmental instability, recurrent disc herniation, spinal canal stenosis or foraminal stenosis. The primary target criteria with regards to safety are: The number, severity and cause of intra- and perioperative complications. The number of significant penetrations of the cortical layer of the vertebral body by the implant as recognized on postoperative CT. The primary target parameters with regards to feasibility are: Performance of the procedure according to the preoperative plan. The planned follow-up is 12 months and the following scores will be evaluated as secondary target parameters with regards to clinical improvement: VAS back pain, VAS leg pain, Oswestry Disability Index, short form - 12 health questionnaire and the Swiss spinal stenosis questionnaire for patients with spinal claudication. The secondary parameters with regards to construct stability are visible fusion or lack thereof and signs of implant loosening, implant migration or pseudarthrosis on plain and functional radiographs. Discussion This trial will for the first time assess the safety and efficacy of guided oblique lumbar interbody fusion. There is no control group, but the results, the outcome and the rate of any complications will be analyzed on the background of the literature on instrumented spinal fusion. Despite its limitations, we expect that this study will serve as the key step in deciding whether a direct comparative trial with another fusion technique is warranted. Trial Registration Clinical Trials NCT00810433